ANALISIS INTEGRATED ENTERPRISES SYSTEM PT. RAMBANG AGRO JAYA METODE HUMAN ORGANIZATION TECHNOLOGY (HOTFIT) - Bunga Intan (LPPM UNIVERSITAS BINA INSAN, 2018)
Abstrak : Enterprises System (IES). Penerapan Integrated Enterprises System (IES) saat ini masih mengalami kendala dan hambatan ditingkat penerimaan pengguna. Masih banyaknya hal yang bersifat operasional dan manajerial, membuat penerapan Integrated Enterprises System (IES) tidak berjalan dengan baik. Penelitian ini melakukan analisis terhadap hasil Evaluasi faktor-faktor kesuksesan penerapan Integrated Enterprises System (IES) dengan menggunakan Model Hot-Fit (Human Organization Technology – Net benefits). Model ini dipilih karena model ini dapat memberikan penjelasan dan memberikan evaluasi faktor penerapan sebuah sistem di PT Rambang Agro Jaya I dari sisi Teknologi (Technology), Manusia (Human), Organisasi (Organization) dan Net benefit. Keberhasilan penerapan Integrated Enterprises System (IES) di PT Rambang Agro Jaya I dipengaruhi oleh adanya dukungan dan dorongan dari pihak manajerial kepada para pengguna Integrated Enterprises System (IES) serta tersedianya kondisi fasilitas yang memadai di lingkungan rumah sakit untuk menggunakan Integrated Enterprises System (IES). Kata kunci: Analisis,Integrated Enterprises System (IES), Model Hot-FitAbstract : PT Rambang Agro Jaya I have been using the technology in data processing, by implementing the Integrated Enterprise System (IES). Application of Integrated Enterprise System (IES) is still experiencing problems and obstacles level of user acceptance. There are still many things that are operational and managerial, making the application of Integrated Enterprise System (IES) is not going well. This study analyzed the results of evaluation factors of the successful implementation of Integrated Enterprise System (IES) using Hot-Fit Model (Human Organization Technology - Net benefits). This model was chosen because this model may provide an explanation and provide an evaluation factor in the implementation of a system Rambang Agro PT Jaya I of the Technology (Technology), Man (Human), Organization (Organization) and Net benefit. The successful implementation of Integrated Enterprise System (IES) in PT Rambang Agro Jaya I was influenced by the support and encouragement from the managerial to users Integrated Enterprise System (IES) and the availability conditions of adequate facilities in the hospital environment for the use of Integrated Enterprise System (IES). Keywords: Analysis, Integrated Enterprise System (IES), Hot-Fit Model